2015
DOI: 10.1073/pnas.1505541112
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater discharges drive high levels of methylmercury in Arctic marine biota

Abstract: Elevated levels of neurotoxic methylmercury in Arctic food-webs pose health risks for indigenous populations that consume large quantities of marine mammals and fish. Estuaries provide critical hunting and fishing territory for these populations, and, until recently, benthic sediment was thought to be the main methylmercury source for coastal fish. New hydroelectric developments are being proposed in many northern ecosystems, and the ecological impacts of this industry relative to accelerating climate changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
148
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(165 citation statements)
references
References 42 publications
(57 reference statements)
10
148
2
Order By: Relevance
“…Other studies of watershed impacts on Hg and MeHg levels in tributaries to Lake Michigan and the Chesapeake Bay (Hurley et al 1995; Lawson et al 2001) similarly found a correlation between MeHg concentration, %MeHg, and the extent of marsh area and/or agricultural activity within the watershed. Recently, Schartup et al (2015) showed the decoupling of MeHg in sediment and water compartments, and the relatively greater importance of water column Hg methylation to MeHg inputs at sites of large freshwater inflow into a stratified shallow Arctic estuary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies of watershed impacts on Hg and MeHg levels in tributaries to Lake Michigan and the Chesapeake Bay (Hurley et al 1995; Lawson et al 2001) similarly found a correlation between MeHg concentration, %MeHg, and the extent of marsh area and/or agricultural activity within the watershed. Recently, Schartup et al (2015) showed the decoupling of MeHg in sediment and water compartments, and the relatively greater importance of water column Hg methylation to MeHg inputs at sites of large freshwater inflow into a stratified shallow Arctic estuary.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that the Delaware River estuary shifts from dominantly sediment sources of increased dissolved MeHg in the ETM (observed in forage fish) to a relatively greater influence of wetland sources of water column MeHg in the lower portion (reflected in shrimp tissue concentrations). These water column dynamics, including interactions and the influence of complexation with changing DOC character and salinity on MeHg bioavailability (Schartup et al 2015), will impact uptake and transfer through the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…It can accumulate and biomagnify at high levels in fish as well as in rice grains, and human consumption can cause neurological damage ( 4 – 7 ). Our understanding of the mechanisms responsible for Hg methylation has greatly improved recently through the identification of the genetic basis ( 1 – 3 ) and factors affecting Hg methylation ( 8 – 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a rainstorm prior to sampling, as was observed in August, could enhance the contribution of the watershed. In June, unidentified sources were again a substantial source of MeHg, but less so for THg, suggesting that while external terrestrial inputs could have contributed MeHg, other processes such as methylation in the water column could be another additional source of MeHg (Ortiz et al, 2015; Schartup et al, 2015), or else there was substantial methylation of Hg and subsequent transport from the upper marsh to the sampling site.…”
Section: Discussionmentioning
confidence: 99%